Beyond Green Packaging: Unveiling the Dynamics of Environmental Consciousness and Sustainable Consumption in Yogyakarta - Nadia Nadia; Della Nanda Luthfiana; Bimo Harnaji; Andika Andika (Dinasti Publisher, 2024)
Amid increasing concerns about plastic pollution and its negative impact on ecosystems, this research explores the relationship between environmental consciousness and the desire of urban consumers in Yogyakarta City to purchase products with eco-friendly packaging. Using the Theory of Planned Behavior (TPB) as a foundation, we aim to unveil the factors influencing consumer preferences toward sustainable packaging alternatives. Through a quantitative approach, this study involved 150 respondents who were selected purposively, with data analysis utilizing Structural Equation Modeling (SEM). Findings indicate a significant relationship between environmental consciousness and positive consumer attitudes towards sustainable packaging, emphasizing the crucial role of environmental consciousness in driving preferences for eco-friendly options. However, consumer attitudes alone do not directly increase the willingness to purchase these products. Instead, subjective norms and perceived behavioral control emerge as the primary determinants, highlighting the strong influence of social pressure and personal efficacy beliefs on sustainable purchasing decisions. This study not only contributes to the theoretical discourse on consumer behavior in environmental sustainability but also offers practical insights for policymakers, businesses, and environmental campaigns in promoting a culture of sustainable consumption through effective communication strategies, policy interventions, and market-based solutions.